Equity Trading Activity and Treasury Bond Risk Premia - Schraeder, Stefanie; Sojli, Elvira; Subrahmanyam, Avanidhar; Tham, Wing W. (Journal of Financial and Quantitative Analysis, 2023)
Abstract We link equity and treasury bond markets via an informational channel. When macroeconomic state shifts are more probable, informed traders are more likely to have valid signals about fundamentals, so that uninformed traders are less willing to trade against informed ones. This implies low volume and high volatility, that is, a high volatility–volume ratio (VVR). Central banks react to state shifts, but their actions are uncertain. Therefore, a higher state shift likelihood implies larger bond risk premia. These arguments together imply that VVR should positively predict bond excess returns. We empirically test and confirm this prediction, both in- and out-of-sample.